Outline of a Proposal to Set up Patents Information System in India - Rajagopalan, T. S. (Journal of Information and Knowledge, 1981)
Briefly touches upon patent systems, the nature of patent information, its use as information sources, and the output of patent literature in India and abroad. After mentioning the correct infrastructure of patent information system, presents a plan for the development of patent information service system, The plan is delineated in relation to its objective, structure and functional aspects. The needed resources are estimated in a nutshell.